ANALYSIS OF ENGLISH VERB-BASED NOMINALS WITH SUFFIXES -ION AND -MENT AND THEIR LITHUANIAN TRANSLATION IN THE EUROPEAN UNION LEGISLATION IN FORCE (Mokslo taikomieji tyrimai / Applied Research, 2022)
This article examines verb-based nominals in translation of the European Union legislation in force. The data for the analysis is collected from the European Union website www.eur-lex.europa.eu. The aim of this paper is to find out the frequency of usage of English verb-based nominals denoting action and process in legal written discourse and to analyze the English nominalizations with the suffixes -ion and -ment as well as their Lithuanian translations in order to show the dominant translation choices. The quantitative analysis of verb-based nominals has been carried out using an automated linguistic program created by Stravinskaitė and Balnionis. This electronic tool has been created only for personal use and specifically for calculating English suffixes. In order to find out the dominant Lithuanian translation equivalents for the English verbbased nominals with the suffixes -ion and -ment, the translation of 200 source language nominalizations has been analyzed. The results show that the use of verb-based nominals is a feature of legal texts in both English and Lithuanian. The quantitative analysis has revealed that the most frequently used English verb-based nominals are those with the suffix -ion (10633 occurrences) and -ment (4446 occurrences). Their most common Lithuanian equivalents are the verb-based nominals with the suffix -imas/-ymas. Direct equivalents, infinitives and participles are less common, while omission and paraphrase appear to be the least common translation options. It has to be noted that despite the criticism from the Lithuanian linguists, the use of the Lithuanian nominals with the suffixes -imas and -ymas in the translation may be advantageous as they lay emphasis on the theme acting as keywords in the text and also make the text concise. Yet, extensive use of such nominalizations might result in abstraction and statics of the legal text. Less frequent translation choices which were observed in the current analysis help to avoid repetition, make the text more vigorous and simplify its complex nature.
Keywords: verb-based nominals; translation; legal discourse; suffixes –ion/-ment